Seabirds as bioindicators of anthropogenic and chemical pollution - Matos, D. M. (2023)
Background: Marine pollution, caused by anthropogenic debris, is a significant environmental issue that has detrimental effects on marine ecosystems ​[1]​. Finding suitable sentinel species of the human impacts on the oceans, is imperative. As top predators, seabirds are considered sentinels of the marine environment ​[2]​. Objective: To provide quantitative data about the distinctive prevalence of anthropogenic pollution on seabirds, five species with different trophic and foraging ecology inhabiting the tropical Atlantic region were used. Methods: The occurrence of anthropogenic debris was assessed using faeces as a proxy for ingestion. Particles were chemically analysed using micro-Fourier transform infrared spectroscopy (mFTIR) ​[3]​. Moreover, preen oil and plasma samples were analysed for Polybrominated Diphenyl ethers (PBDEs) and methoxylated PBDEs (MeO-PBDEs), through with gas chromatography–mass spectrometry (GC-MS/MS) ​[4]​. Results: There were found 438 items suspected of anthropogenic origin, mostly fragments and fibres in all species. Phaethon aethereus (PA n=61), Calonectris edwardsii (CE n=119) and Sula leucogaster (SL n=82) presented the highest frequency occurrence (FO: 51%, 49%, 48%), while Bulweria bulwerii (BB =86) and Puffinus lherminieriboydi (PB n=86) the lowest (FO: 30%, 36%) of anthropogenic particles. Particles revealed a high diversity of polymers, from cellulosic particles to synthetic plastics. PBDEs and MeO-PBDEs were detected in all species and matrices, whereby preen oil had higher concentrations and variety of congeners than plasma. PB had the lowest chemical concentrations in both tissues compared to other species. Moreover, it was not found any correlation between chemical compounds concentration and the number or occurrence of anthropogenic particles. However, particles and chemical compounds were more prevalent in species that explore areas associated to anthropogenic activities. Conclusions: Overall, anthropogenic pollution is transversal to all species, ranging from particle ingestion to chemical compounds. We considered that it is necessary to continue monitoring the impacts of global anthropogenic pollution considering the declines in seabirds’ population.